Evolutionary aspects of social strategies - Royo García, Pilar (Pulso. Revista de educación, 2004)
The article initially outlines the development of constructs and processes that are significant for exploring the evolution of social strategies. Specifically, it focuses on the development of skills such as coordinating diverse social perspectives, the evolution of the concept of friendship and interpersonal awareness, and the age-related changes observed in studies exploring the conceptualisation of social conflict and the social goals children establish in their interactions with peers. Subsequently, the article delves into more specific research on the acquisition and development of social strategies, followed by a discussion of key findings and conclusions on this subject.